Zonun's regime (35% glycolic acid peel with microneedling followed by tretinoin 0.05% plus glycolic acid 12% application followed by salicylic acid 30% peeling) for treatment of acne scars: a pilot study - Zonunsanga (Our Dermatology Online, 2015)
Introduction: Acne scars are the result of inflammation within the dermis brought on by acne. The scar is created by the wound trying to heal itself resulting in too much collagen in one spot. Current treatment available are not much satisfactory. Microneedling injure the dermis, thereby stimulating collagen formation. Glycolic acid acts as vehicle for delivery of drugs to dermis: in addition to that, it also has a role in collagen induction. Tretinoin helps in collagen formation. Salicylic acid remodel the superficial skin after the treatment. Material and Methods: A total of 4 patients in which 3 out of 4 patient, grade 3 acne scars and 1 out of 4 had grade 2 scar were treated with the regime. After taking consent 35% Glycolic acid peeling was done followed by microneedling. From the next day 12% Glycolic acid plus 0.05% Tretinoin is applied once a day for 2 months. After 2 months 30% Salicylic acid peeling is done. Photographs were taken before treatment, after 1 month and after 2 months of completion of the therapy and compared. Objective assessment was done according to Global Acne Scarring Classification. Result: subjectively 2 patients reported excellent response and 2 patients reported good response. Objectively, all patients showed good to excellent response. Conclusion: Zonun's regime may be effective for treatment of acne scars.